Costs of topical treatment of pressure ulcer patients - Cynthia Carolina Duarte Andrade; Cláudia Fernanda dos Santos Calixto de Almeida; Walkíria Euzébio Pereira; Márcia Mascarenhas Alemão; Cristina Mariano Ruas Brandão; Eline Lima Borges (SciELO, 2016)
Abstract OBJECTIVE To evaluate the costs of a topical treatment of pressure ulcer (PU) patients in a hospital unit for treatment of chronic patients in 2014. METHOD This is an activity-based costing study. This method encompasses the identification, measurement and pricing of physical and human resources consumed for dressings. RESULTS Procedure costs varied between BRL 16.41 and BRL 260.18. For PUs of the same category, of near areas and with the same type of barrier/adjuvant, the cost varied between 3.5% and 614.6%. For most dressings, the cost increased proportionally to the increase of the area and to the development of PU category. The primary barrier accounted for a high percentage of costs among all items required to the application of dressings (human and material resources). Dressings applied in sacral PUs had longer application times. CONCLUSION This study allowed us to understand the costs involved in the treatment of PUs, and it may support decision-makers and other cost-effectiveness studies.